UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA BANGUN RUANG MENGGUNAKAN METODE MIND MAP - Herdiaswati, Lurit (Jurnal Likhitaprajna, 2018)
Mathematics subjects are generally seen as difficult for students because they are difficult to understand, full of symbols and approaches to mathematics learning that are less attractive. This makes students bored and reluctant to learn mathematics. The design of this study is classroom action research (CAR). In the first cycle the percentage achieved from all aspects observed resulted in data 46.7% aspects fulfilled. After continuing in the second cycle the percentage of aspect fulfillment became 86.7% or in the high category.Keywords: learning outcomes, mathematics, mind map